Synthesis and biodegradation studies of new copolymers based on sucrose derivatives and styrene - Barros, M. Teresa; Petrova, Krasimira T.; Singh, Raj P. (European Polymer Journal, 2010)
Novel unsaturated esters of sucrose were synthesised directly and in good yields from sucrose using a simple, mild, and selective Mitsunobu procedure. These regioisomerically pure vinyl sugars have been copolymerised with styrene by a free radical process, yielding unbranched linear polymer materials with pendant sucrose moieties. Their physical properties indicate that these polymers have potential technological relevance as amphiphilic and biodegradable materials. Biodegradation tests on the copolymer samples by a fungal (Aspergillus niger) culture method showed a fungal growth >= 60%, indicating good biodegradability and that the copolymers were partiallybio-assimilated during microbial attack. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable copolymers; Biodegradation culture test; free radical copolymerization; Vinyl sucrose ester monomers

Synthesis of hydrophilic and amphiphilic acryl sucrose monomers and their copolymerisation with styrene, methylmethacrylate and alpha- and beta-pinenes - Barros, Maria Teresa; Petrova, Krasimira T.; Singh, Raj P. (International Journal of Molecular Sciences, 2010)
Herein, we report the synthesis of monomethacryloyl sucrose esters, and their successful free radical homo- and co-polymerisation with styrene, methylmethacrylate, alpha- and beta-pinene. The chemical, physical, structural and surface chemical properties of these polymers, containing a hydrophobic olefin backbone and hydrophilic sugar moieties as side chains, have been investigated. Biodegradation tests of the copolymer samples by a microbial fungal culture (Aspergillus niger) method showed good biodegradability. The chemical structure and surface chemistry of the synthesized homo- and co-polymers demonstrate their potential technological relevance as amphiphilic and biodegradable polymers.
Keywords: Biodegradable copolymers; Biodegradation culture test; free radical copolymerization; Vinyl sucrose ester monomers

Prediction of reactivity ratios in free radical copolymerization from monomer resonance-polarity (Q-e) parameters: genetic programming-based models - Shrinivas, K.; Kulkarni, Rahul P.; Shaikh, Saif; Ghorpade, Ravindra V.; Vyas, Renu; Tambe, Sanjeev S.; Ponrathnam, S.; Kulkarni, Bhaskar D. (International Journal of Chemical Reactor Engineering, 2016)
The principal deficiency of the widely utilized Alfrey-Price (AP) scheme for computing reactivity ratios in the widely used free radical copolymerization is that it ignores important factors, such as the steric effects. This often leads to inaccurate reactivity ratio predictions by AP model. Accordingly, in this study, exclusively data-driven, Q-e parameter-based new models have been developed for the reactivity ratio prediction in free radical copolymerization. In the model development, a novel artificial intelligence formalism known as ``genetic programming (GP)'' that performs symbolic regression has been employed. The GP-based models possess a different functional form than AP model. Further, parameters of GP-based models were fine-tuned using Levenberg-Marquardt (LM) nonlinear regression method. A comparison of AP, GP and GP-LM as well as artificial neural network (ANN)-based models indicates that GP and GP-LM models exhibit superior reactivity ratio prediction accuracy and generalization performance (with correlation coefficient magnitudes close to or greater than 0.9) when compared with AP and ANN models. The GPbased reactivity ratio prediction models developed here due to their higher accuracy and generalization capability have the potential of replacing the widely used AP models.
Keywords: Alfrey-Price scheme; free radical copolymerization; genetic programming; reactivity ratio; symbolic regression